COMMUNITY VOICES ON THE URBAN FARMING MOVEMENT DURING THE COVID-19 PANDEMIC: A REFLECTIVE STUDIES - Ayuni Kusumawati; Gabe Arif Ditama Sinaga; Yani Kurniawan; Nur Aisyah Aminy; Hafida Ruminar (Socio-Economics/Agribusiness Department, 2022)
Urban farming activities in Malang City have increased during the COVID-19 pandemic. This study responds to the threat of a food crisis due to the continued impact of the COVID-19 pandemic. Massive implementation of urban farming can provide different perceptions and goals depending on the characteristics of each individual, including differences in occupation, gender, and age. This research aimed to investigate the perspective on the implementation of urban farming during the COVID-19 pandemic. It is a critical reflection study to determine what factors affected the implementation of urban farming in supporting food security in Malang City. The study was conducted in Lowokwaru District, Sukun District, and Blimbing District, with 30 participants. The findings indicated that the success of urban farming in Malang City was affected by various factors. For instance, the growing interest in urban farming, urban farming contests, and social activities. It also could support food security in urban areas during the COVID-19 pandemic. In addition, the existence of farmer group communities and the role of the government and the wider community can contribute to the success of urban farming.